PENGGUNAAN TEKNOLOGI DALAM PENGEMBANGAN ASESMEN DIGITAL PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN SARIPIN TASIKMALAYA - Kosasih, Fitriyani; Setyaningrum, Wulan; Fathonah, Siti; Hasanah, Cucu; Saepullah, Aep; Surya Zulkifli, Arief; Sulaeman, Diki; M Sukron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of technology in developing digital assessments in Islamic Religious Education learning at SDN Saripin Tasikmalaya and identify obstacles that arise in its implementation. This study used a qualitative descriptive method. Data were collected through semi-structured interviews with Islamic Religious Education teachers as key informants, and was supported by literature review. The results indicate that technology integration through digital platforms such as Quizizz and Google Forms, supported by the use of Smart TVs, has increased data processing efficiency, assessment accuracy, and student motivation and enthusiasm in the evaluation process. However, the effectiveness of digital assessments still faces challenges such as limited internet infrastructure, unequal availability of digital devices, and the need to improve digital literacy competencies for educators. This study concludes that digitalizing assessments is a strategic step in improving the quality of learning that adapts to the demands of the digital era.